2 - Reclaiming Urban Youth Identity through Language in Kenya: The Case of Koch FM Radio - Ojwang, Benson Oduor (Africa Development, 2017)
Kenya’s urban youths in Nairobi’s informal and low income settlements have had to contend with an identity crisis, economic deprivation, marginalization in leadership and governance and general stigmatization. Moreover, they have borne a heavy burden both as victims and perpetrators of crime, wanton sex trade and drug abuse. This has led to the emergence of a special language variety in the form of an urban slang (Sheng) that the youth initially used to exclude their parents and the authorities from their perceived criminal acts. However, since the enactment of a new constitution that has expanded the democratic space and created broader awareness of individual rights and liberties, Kenya’s urban youth in Nairobi have given new roles to Sheng by making it a symbol of youth’s autonomy and creativity. This article uses the case of the youth-initiated Koch FM which is a model urban community radio station that primarily uses urban slang in its presentations. Through this station, the socio-economically disadvantaged youths create and maintain social networks in the form of support groups, theatre and income generating clubs with the objective of creating wealth, thereby boosting identity through assertive self-expression. The youth can then articulate and influence policy on social, political and economic affairs by sharing information on health, HIV/AIDS, political representation and governance roles. This case study demonstrates that a common language can be an effective unifier since it transcends social, economic, religious, ethnic, political and gender barriers.